Emotional Condition and Physical Activity of First-year Female Students at Medical College During the Academic Year - Nataliia Semenova; Anatolii Mahlovanyi (OVS LLC, 2017)
The objective isto establish emotional state changes among female students during the academic year regarding available physical activity. Material & methods: the study involved 65 first year femalestudents of medical college at Danylo Halytskyi Lviv National Medical University.  To achieve the tasks set the study relied on the following methods: analysis and synthesis of scientific and technical literature, pedagogical observation, methods of mathematical statistics (t-Student test for independent samples), SAN method. Results: no reliable differences found when comparing indicators of activity and mood at the beginning and end of the academic year. The obtained results of the survey indicate medium and high evaluationof SAN categories at low levels of physical activity. Conclusions: state of health, activity and mood levelswere rated with middle and high scoresbyfemale students. SAN evaluation dynamics has been lowering during the academic year, and the activity level of female students was significantly lower than that ofstate of health as well as mood. The resulting index of activity level as emotional characteristic largely reflects low physical activity of female students.